Straightening the Eyes Doesn't Rebalance the Brain - Zhou, Jiawei; Wang, Yonghua; Feng, Lixia; Wang, Jiafeng; Hess, Robert F. (Frontiers in Human Neuroscience, 2017)
Surgery to align the two eyes is commonly used in treating strabismus. However, the role of strabismic surgery on patients’ binocular visual processing is not yet fully understood. In this study, we asked two questions: 1. Does realigning the eyes by strabismic surgery produce an immediate benefit to patients’ sensory eye balance? 2. If not, is there a subsequent period of “alignment adaptation” akin to refractive adaptation where sensory benefits to binocular function accrue? Seventeen patients with strabismus (mean age: 17.06 ± 5.16 years old) participated in our experiment. All participants had normal or corrected to normal visual acuity (LogMAR < 0.10) in the two eyes. We quantitatively measured their sensory eye balance before and after surgery using a binocular phase combination paradigm. For the seven patients whose sensory eye balance was measured before surgery, we found no significant change (t(6) = -0.88; p = 0.41) in the sensory eye balance measured 0.5-1 months after the surgery, indicating that the surgical re-alignment didn’t by itself produce any immediate benefit for sensory eye balance. To answer the second question, we measured 16 patients’ sensory eye balance at around 5-12 months after their eyes had been surgically re-aligned and compared this with our measurements 0.5-1 months after surgery. We found no significant change (t(15) = -0.89; p = 0.39) in sensory eye balance 5-12 months after the surgery. These results suggest that strabismic surgery while being necessary is not itself sufficient for re-establishing balanced sensory eye dominance.